Therapeutic Potential of Astaxanthin Against Cadmium-Induced Hepatic Failure: An Experimental Study: Astaxanthin and Cadmium Hepatotoxicity - Mir Mohammadrezaei, Fereshteh; Ghasempour Ganji, Zeinab; Nili-Ahmadabadi, Amir; Hajizadeh Moghaddam, Akbar (Iranian Journal of Pharmaceutical Sciences, 2022)
Cadmium is a toxic metal that can lead to liver failure in humans and animals. Astaxanthin (ASX) is one of the well-known xanthophyll carotenoids in food that has remarkable antioxidant properties. Hence, this study investigated the effect of ASX against cadmium-induced hepatic failure. Twenty-four mice were divided into four groups of six each and treated intraperitoneally as follows: group 1 (sham) received normal saline and olive oil; group 2 received 10 mg/kg/day of ASX; groups 3 and 4 were treated with cadmium (1 mg/kg/day) and ASX (10 mg/kg/day) + cadmium (1 mg/kg/day), respectively. After 14 consecutive days, mice were sacrificed and blood and liver samples were isolated for histopathological and biochemical experiments. Our findings showed a significant increase in serum alanine aminotransferase level, as a hepatic marker, following cadmium administration (p < 0.05). In this regard, cadmium led to hepatic leukocyte infiltration, dilated sinusoids, and increased hepatic metallothionein level (p < 0.01). Following the administration of ASX, a significant improvement was found in the metallothionein level and hepatic enzymes alongside histopathologic alterations. The present study revealed that the administration of ASX could prevent cadmium-induced hepatic failure, which may be related to the antioxidant properties of this carotenoid.